Achievement of Release Mode under Combinational Stimuli by Acid and Reduction for Reduced Adverse Effect in Antitumor Efficacy. Issue 10 (October 2016) - Song, Meifang; Xue, Yanan; Lin, Xiao; Xia, Xiaoyang; Chen, Lidi; Zhang, Liujie; Yu, Bo; Long, Sihui; Huang, Shiwen; Yu, Faquan
Abstract : Superparamagnetic nanogels with release mode under combinational stimuli by acid and reduction for achievement of reduced adverse effect in antitumor efficacy are fabricated via electrostatic interactions and the formation of disulfide bonds. Abstract : To reduce the adverse effect in antitumor therapy, a superparamagnetic doxorubicin (DOX)‐loaded nanogel with the release mode under the combinational stimuli present in intracellular environments of solid tumors is presented. Dextran is first modified to involve both thiol groups and carboxyl groups. The dextran derivative is then covalently coupled with previously thiolated and aminated magnetic iron oxide nanoparticles through both the linkage of disulfide bond and electrostatic interaction. Upon the optimal conditions, a nanogel is fabricated via the dual cross‐linking. The nanogel features the targeting release under combinational stimuli by acid and reduction environment with low release level in healthy tissues. In vitro release profiles reveal these release modes as expected. Cytotoxicity assay exhibits a much lower toxicity of the DOX‐loaded nanogel to COS‐7 cells than free DOX. Prussian blue staining and confocal laser scanning microscopy observation reveal the cellular uptake and subcellular release in nuclei of the nanogel. In vivo study exhibits that the nanogel presented 67.3% of inhibition rate of tumor growth and a healthy appearance. The present nanogel expresses high efficacy with low systemic adverse effect and is thus believed to offer a promising candidate for highly effective cancer therapy.